Impacts of climate change and land-use scenarios on Margaritifera margaritifera, an environmental indicator and endangered species - Santos, R.M.B. (2015)
In this study, we assess the impacts of future climate and land-use in the Beça River (northern Portugal) under different scenarios and how this will translate into the conservation status of the endangered pearl mussel Margaritifera margaritifera (Linnaeus, 1758). This species is currently present in several stretches of the Beça River that still hold adequate ecological conditions. However, the species is threatened by projected declines in precipitation for the 21st century, with implication on the river flows and water depths that might decrease below the species requisites. This situation could be especially critical during summer conditions since the ecological flows may not be assured and several river stretches may be converted into stagnant isolated pools. The habitat connectivity will also be affected with reverberating effects on the mobility of Salmo trutta, the host of M. margaritifera, with consequences in the reproduction and recruitment of pearl mussels. In addition, human-related threats mostly associated with the presence of dams and an predicted increases in wildfires in the future. While the presence of dams may decrease even further the connectivity and river flow, with wildfires the major threat will be related to the wash out of burned areas during storms, eventually causing the disappearance of the mussels, especially the juveniles. In view of future climate and land-use change scenarios, conservation strategies are proposed, including the negotiation of ecological flows with the dam promoters, the replanting of riparian vegetation along the water course and the reintroduction of native tree species throughout the catchment.